REFLEXIONES EN TORNO A LA ENSEÑANZA DE LA HISTORIA EN COLOMBIA: UN BREVE BALANCE HISTORIOGRÁFICO - Restrepo Zapata, Juan David (2018)
The article makes a reflection of the teaching of history in Colombia from the compilation of the main manuals used by the State to teach History courses in the country. It is analyzed the different ways of approaching history throughout of the Colombian republican life, for identify aspects of the national construction, of the political use of this one, and of the disciplinary advance of the history that was written and taught, this without ignoring the international context from which Colombia was influenced. In this sense, this study aims to offer a panoramic view of the development and evolution of the teaching of history in the country, taking into account the processes of national life, educational and political influences and the meaning of teaching this social science in a country as complex as Colombia.